Accelerated degradation of Al3+ doped ZnO thin films using damp heat test - Litzov, Ivan; Azimi, Seyed Hamed; Matt, Gebhard; Kubis, Peter; Stubhan, Tobias; Popov, Georgi; Brabec, Christoph (Organic Electronics, 2014)
Two different types of aluminum-doped zinc oxide (AZO) thin films were fabricated using low cost sol-gel technique. By applying damp heat testing, the optical and electrical properties of those films were investigated under the influence of accelerated degradation from moisture or moisture vapor. Complementary measurements of optical transmittance, work function, and conductivity allowed exploring the degradation of AZO thin films and the corresponding OPV devices. We found that optical properties like transmittance, absorption coefficient, and band gap are not influenced by temperature and moisture. However, an increase in the work function, and a decrease in the conductivity of AZO films were observed upon damp heat exposure indicating the formation of a barrier or depletion layer at the metal oxide semiconductor interface. © 2013 Elsevier B.V. All rights reserved.
Keywords: Aluminum-doped zinc oxide; Conductivity; Damp heat test; Work function